An electrostatically regulated organic self-assembly for rapid and sensitive detection of heparin in serum. Issue 32 (27th July 2021) - He, Zhixiao; Nie, Hailiang; Cui, Jie; Zhang, Xiaoling; Yang, Xiaoxi; Li, Cuiping; Yan, Hongyuan
Abstract : A self-assembly composed of a long-wavelength double-charged cationic fluorescent dye is used for rapid, sensitive and reversible detection of heparin in serum. Abstract : Heparin (Hep) is a highly negatively charged linear glycosaminoglycan involved in various physiological processes, especially blood coagulation. Hep is also a first-line drug for anticoagulation and prevention of thromboembolism, but its overdose will cause serious side effects. Herein, we designed a long-wavelength double-charged cationic fluorescent probe PYPN, and studied its aggregation state and detection performance for Hep. PYPN was readily synthesized through a one-step reaction without complicated purification. In aqueous medium, PYPN molecules with an amphiphilic structure spontaneously form nano-assemblies, which can be immediately decomposed by Hep due to the formation of a PYPN–Hep complex based on electrostatic attraction. The assembly shows a fast, sensitive and ratiometric fluorescence response to Hep, without being obviously interfered by other compounds. In various serum matrices, the fluorescence intensity ratio F 610 / F 470 has a good linearity with Hep concentration (0–12 μg mL −1 ), and the detection limit (0.11–0.12 U mL −1 ) is lower than the minimum concentration (0.2 U mL −1 ) used in clinical treatment. Our study provides an easy-to-prepare and feasible tool for the selective and sensitive quantification of Hep in serum.